2017
DOI: 10.1111/iju.13296
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic implantation of artificial urinary sphincter in women with intrinsic sphincter deficiency: Mid‐term outcomes

Abstract: Herein we report one of the largest series with the longest follow up evaluating the outcomes of laparoscopic artificial urinary sphincter implantation in female patients. This approach seems to be a safe and effective treatment option for patients with intrinsic sphincter deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
0
14
0
4
Order By: Relevance
“…The aim of the present study was to update and analyse the safety and outcomes of laparoscopic AUS implantation in women with SUI caused by ISD in our 13‐year single‐centre experience.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study was to update and analyse the safety and outcomes of laparoscopic AUS implantation in women with SUI caused by ISD in our 13‐year single‐centre experience.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the surgical approach may have a significant impact on outcomes, as suggested by the promising results of most laparoscopic and robotic series . Indeed, while those studies assessed the early learning curve of this new technique, they reported outcomes similar to many large open series.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the subsequent management of women who experienced device explantation for erosion or infection were too sparse to be analyzed accurately for the purpose of this systematic review. In the few series describing the management of these patients, three options were reported: ileal conduit, repeat implantation, and status quo . While the feasibility of AUS reimplantation has been demonstrated by several series in male patients, more robust data are needed regarding the outcomes of subsequent anti‐incontinence procedures after explantation in female patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations